THE PROPOSED HAGUE CONVENTION ON JURISDICTION, RECOGNITION AND ENFORCEMENT OF JUDGMENTS - Smith, Bradbrooke (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 1999)
A new international agreement on juridiction and foreign judgments in civil and commercial matters is needed because the Hague Convention of 1971 has proven unworkable. The Brussels Convention of 1968 and the Lugano Convention of 1988 were helpful in resolving jurisdictional issues in the European context, but because of the lack of reciprocity in the european approach, even though North American courts have a liberal approach towards the recognition of foreign judgements, North American judgements are at a disadvantage before European courts. The United States’ initiative in promoting a consistent international approach to the enforcement of foreign judgments may lead to a new Hague Convention.The author discusses procedures of the Hague Conference on Private International Law and the work of the Special Commission, which is charged with the task of working up a draft text for a new judgments convention. The author’s view is that decisions made at the Hague Conference will have real impacts on the practice of international lawyers and their clients. He identifies key members of the Canadian delegation to the Special Commission and encourages practitioners to contact the members so their concerns and ideas will be considered during the drafting process of the convention.